Prevalence of serum immunoglobulin E against cross‐reactive carbohydrate determinants in allergic and nonallergic horses, and its impact on polysensitisation in serum allergen tests. Issue 4 (30th May 2022) - Hopke, Kaitlin; Coleman, Michelle; Kneese, Eric; Dominguez, Brandon; Diesel, Alison; Patterson, Adam
Abstract: Background: The existence of antibodies against cross‐reactive carbohydrate determinants (CCDs) has been studied extensively in humans, and more recently, in dogs and cats. These antibodies can reduce the specificity of in vitro serum allergen tests. Objectives: To investigate the prevalence of anti‐CCD immunoglobulin (Ig)E in both allergic and nonallergic horses as well as evaluate its potential impact on serum allergen testing. Animals: Twenty‐one allergic and 21 nonallergic horses. Methods and Materials: Sera were analysed for anti‐CCD IgE utilising a commercial CHO enzyme‐linked immunosorbent assay (ELISA). An allergen specific Fc‐ε receptor ELISA then was performed to evaluate polysensitisation, both with and without the addition of a proprietary anti‐CCD blocking solution. Results: Antibodies against CCD were detected in 30 of 42 horses. There was no statistically significant difference ( p = 0.18) between the allergic and healthy groups in regard to anti‐CCD prevalence. Horses with anti‐CCD IgE exhibited more polysensitisation on serum allergen tests than horses without anti‐CCD IgE in all allergen groups except mites. Polysensitisation was statistically significant at the 95% confidence interval for grasses ( p <0.03), weeds ( p = 0.02) and stinging insects ( p = 0.0005). This was found to be true across both study groups. Inhibition with an anti‐CCD blocking solution resulted in a 43% average reduction in polysensitisation. Conclusion and clinical importance: The prevalence of anti‐CCD IgE of horses in this study coincides with the prevalence detected in pollen‐sensitised people. Horses with anti‐CCD IgE exhibited more positive reactions on serum allergen tests. By minimising potential artifactual polysensitisation, inclusion of an anti‐CCD blocker may facilitate identification of allergen‐specific IgE. Abstract : Background – The existence of antibodies against cross‐reactive carbohydrate determinants (CCDs) has been studied extensively in humans, and more recently, in dogs and cats. These antibodies can reduce the specificity of in vitro serum allergen tests. Objectives – To investigate the prevalence of anti‐CCD immunoglobulin (Ig)E in both allergic and nonallergic horses as well as evaluate its potential impact on serum allergen testing. Conclusion and clinical importance – The prevalence of anti‐CCD IgE of horses in this study coincides with the prevalence detected in pollen‐sensitised people. Horses with anti‐CCD IgE exhibited more positive reactions on serum allergen tests. By minimising potential artifactual polysensitisation, inclusion of an anti‐CCD blocker may facilitate identification of allergen‐specific IgE. Résumé: Contexte ‐ L'existence d'anticorps contre les déterminants glucidiques à réaction croisée (CCD) a été largement étudiée chez l'homme et, plus récemment, chez le chien et le chat. Ces anticorps peuvent réduire la spécificité des tests d'allergènes sériques in vitro . Objectifs – Étudier la prévalence de l'immunoglobuline anti‐CCD (Ig)E chez les chevaux allergiques et non allergiques et évaluer son impact potentiel sur les tests d'allergènes sériques. Animaux – Vingt et un chevaux allergiques et 21 chevaux non allergiques. Matériels et méthodes ‐ Les sera ont été analysés pour les IgE anti‐CCD en utilisant un dosage immuno‐enzymatique CHO commercial (ELISA). Un ELISA du récepteur Fc‐ε spécifique à l'allergène a ensuite été réalisé pour évaluer la polysensibilisation, avec et sans l'ajout d'une solution exclusive de blocage anti‐CCD. Résultats – Des anticorps anti‐CCD ont été détectés chez 30 des 42 chevaux. Il n'y avait pas de différence statistiquement significative ( P = 0, 18) entre les groupes allergiques et sains en ce qui concerne la prévalence anti‐CCD. Les chevaux avec des IgE anti‐CCD ont montré plus de polysensibilisation aux tests d'allergènes sériques que les chevaux sans IgE anti‐CCD dans tous les groupes d'allergènes à l'exception des acariens. La polysensibilisation était statistiquement significative à l'intervalle de confiance de 95 % pour les graminées ( P < 0, 03), les herbacées ( P = 0, 02) et les insectes piqueurs ( P = 0, 0005). Cela s'est avéré vrai dans les deux groupes d'étude. L'inhibition avec une solution de blocage anti‐CCD a entraîné une réduction moyenne de 43 % de la polysensibilisation. Conclusion et importance clinique – La prévalence des IgE anti‐CCD des chevaux dans cette étude coïncide avec la prévalence détectée chez les personnes sensibilisées au pollen. Les chevaux avec des IgE anti‐CCD ont présenté des réactions plus positives aux tests d'allergènes sériques. En minimisant la polysensibilisation artificielle potentielle, l'inclusion d'un bloqueur anti‐CCD peut faciliter l'identification des IgE spécifiques de l'allergène. Resumen: Introducción ‐ la existencia de anticuerpos contra los determinantes de carbohidratos de reacción cruzada (CCD) se ha estudiado ampliamente en humanos y, más recientemente, en perros y gatos. Estos anticuerpos pueden reducir la especificidad de las pruebas de alérgenos séricos in vitro . Objetivos – Investigar la prevalencia de inmunoglobulina (Ig)E anti‐CCD tanto en caballos alérgicos como no alérgicos, así como evaluar su impacto potencial en las pruebas de alérgenos séricos. Animales ‐ veintiún caballos alérgicos y 21 no alérgicos. Métodos y materiales ‐ los sueros se analizaron para detectar IgE anti‐CCD utilizando un ensayo comercial inmunoabsorbente ligado a enzimas (ELISA) para CHO. A continuación, se realizó un ELISA del receptor Fc‐ε específico del alérgeno para evaluar la polisensibilización, con y sin la adición de una solución de bloqueo anti‐CCD patentada. Resultados ‐ se detectaron anticuerpos contra CCD en 30 de 42 caballos. No hubo diferencia estadísticamente significativa ( P = 0, 18) entre los grupos alérgicos y sanos con respecto a la prevalencia de anti‐CCD. Los caballos con IgE anti‐CCD exhibieron más polisensibilización en las pruebas de alérgenos séricos que los caballos sin IgE anti‐CCD en todos los grupos de alérgenos excepto los ácaros. La polisensibilización fue estadísticamente significativa en el intervalo de confianza del 95 % para pastos ( P < 0, 03), malas hierbas ( P = 0, 02) e insectos picadores ( P = 0, 0005). Se encontró que esto fue similar en ambos grupos de estudio. La inhibición con una solución de bloqueo anti‐CCD resultó en una reducción promedio del 43 % en la polisensibilización. Conclusión e importancia clínica – La prevalencia de IgE anti‐CCD de los caballos en este estudio coincide con la prevalencia detectada en personas sensibilizadas al polen. Los caballos con IgE anti‐CCD exhibieron más reacciones positivas en las pruebas de alérgenos en suero. La inclusión de un bloqueador anti‐CCD puede facilitar la identificación de IgE específica de alérgeno al minimizar la posible polisensibilización artificial. Zusammenfassung: Hintergrund ‐Das Auftreten von Antikörpern gegen kreuz‐reagierende Kohlenhydrat Determinanten (CCDs) ist beim Menschen ausführlich untersucht und jüngst geschah dies auch bei Hunden und Katzen. Diese Antikörper können die Spezifität von in vitro Serum Allergentests reduzieren. Ziele – Eine Untersuchung der Prävalenz von Anti‐CCD Immunglobulin (Ig) E bei allergischen wie auch bei nicht allergischen Pferden sowie eine Evaluierung des potenziellen Einflusses auf Serum Allergietests. Tiere – Einundzwanzig allergische und 21 nicht allergische Pferde. Methoden und Materialien – Sera wurden unter Verwendung eines kommerziellen CHO Enzyme Linked Immunosorbent Assays (ELISA) auf Anti‐CCD IgE analysiert. Danach wurde ein Allergen‐spezifischer Fc‐ɛ Rezeptor ELISA zur Evaluierung einer Polysensibilisierung, sowohl mit als auch ohne Zusatz eines gewerblichen Anti‐CCD Blockierungs‐Reagens, durchgeführt. Ergebnisse – Antikörper gegen CCD wurden bei 30 von 42 Pferden festgestellt. Es bestand in Bezug auf die Prävalenz von Anti‐CCD kein statistisch signifikanter Unterschied ( P = 0, 18) zwischen der allergischen und der gesunden Gruppe. Pferde mit Anti‐CCD zeigten im Serum Allergentest eine höhere Polysensibilisierung als Pferde ohne Anti‐CCD in allen Allergengruppen außer bei Milben. Eine Polysensibilisierung war bei einem 95%igem Konfidenzintervall bei den Gräsern ( P < 0, 03), Unkräutern ( P = 0, 02) und den stechenden Insekten ( P = 0, 0005) statistisch signifikant. Das galt für beide Studiengruppen. Die Inhibition mit einer Anti‐CCD Blockierungslösung resultierte durchschnittlich in einer 43%igen Reduzierung der Polysensibilisierung. Schlussfolgerungen und klinische Bedeutung – Die Prävalenz von Anti‐CCD IgE bei Pferden in dieser Studie stimmt mit jener von Pollen‐allergischen Menschen überein. Pferde mit Anti‐CCD IgE zeigten mehrere positive Reaktionen bei den Serum Allergietests. Durch eine Minimierung der potenziellen Artefakte bei der Polysensibilisierung könnte der Einsatz eines Anti‐CCD Blockers die Identifizierung von Allergen‐spezifischem IgE ermöglichen. 概要: 背景‐交差反応性糖鎖決定基 (CCD) に対する抗体の存在は、ヒトで広く研究されており、最近ではイヌおよびネコでも研究されている。これらの抗体は、in vitro 血清アレルゲン検査の特異性を低下させる可能性がある。 目的 – 本研究の目的は、アレルギー馬および非アレルギー馬の抗CCD免疫グロブリン (Ig)Eの有病率を調べるとともに、血清アレルゲン検査に及ぼす潜在的影響を評価することであった。 材料と方法 ‐ 血清は、市販の CHO 酵素結合免疫吸着測定法 (ELISA) を用いて抗 CCD IgE を解析した。その後、アレルゲン特異的な Fc‐ε 受容体 ELISA を実施し、独自の抗 CCD ブロッキング溶液を添加した場合と添加しない場合の両方で多感作を評価した。 結果 ‐ CCDに対する抗体は42頭中30頭で検出された。抗CCD抗体の陽性率は、アレルギー群と健常群の間に統計学的有意差は認められなかった (P = 0.18) 。抗CCD IgEを有する馬は、ダニを除くすべてのアレルゲン群において、抗CCD IgEを有しない馬よりも血清アレルゲン検査で多感作を呈した。イネ科植物 (P < 0.03) 、雑草 (P = 0.02) 、刺咬虫(P = 0.0005) では95%信頼区間で多感作が統計的に有意であった。これは、両方の研究グループにわたって当てはまることがわかった。抗CCDブロッキング溶液による阻害は、多感作を平均43%減少させる結果となった。 結論と臨床的重要性 – 本研究における馬の抗 CCD IgE の有病率は、花粉に感作された人々で検出された有病率と一致する。抗CCD IgEを有する馬は、血清アレルゲン検査でより多くの陽性反応を示した。人為的な多感作の可能性を最小限にするため、抗CCDブロッカーを含めることにより、アレルゲン特異的IgEの同定を容易にすることができるかもしれない。 摘要: 背景‐已在人类以及最近在犬和猫中广泛研究了抗交叉反应性碳水化合物决定簇(CCDs)抗体的存在。这些抗体可以降低体外血清过敏原检测的特异性。 目的‐研究抗CCD免疫球蛋白(Ig)E在过敏和非过敏马中的流行率, 并评价其对血清变应原检测的潜在影响。 动物–21匹过敏马和21匹非过敏马。 方法和材料‐使用市售CHO酶联免疫吸附试验(ELISA)分析血清中的抗CCD IgE。然后进行变应原特异性Fc‐ε受体ELISA, 在加入和不加入专有抗CCD封闭液的情况下评价多敏性。 结果‐在42匹马中的30匹中检测到抗CCD抗体。过敏组和健康组在抗CCD流行率方面无统计学差异(P = 0.18)。在除螨虫外的所有变应原组中, 与无抗CCD IgE的马相比, 抗CCD IgE的马在血清变应原检测中表现出更多的多敏性。在95%置信区间下, 人工草(P < 0.03)、杂草(P = 0.02)和蛰刺类昆虫(P = 0.0005)的多敏性具有统计学显著性。发现两个研究组均是如此。用抗CCD封闭液抑制导致多敏性平均降低43%。 结论和临床重要性‐本研究中马抗CCD IgE的流行率与花粉致敏人群中检测到的流行率一致。抗CCD IgE的马在血清变应原试验中表现出更多的阳性反应。通过尽量减少潜在的人为多敏作用, 纳入抗CCD阻断剂可能有助于识别变应原特异性IgE。 Resumo: Contexto – A existência de anticorpos contra determinantes de carboidratos de reação cruzada (CCDs) tem sido estudada extensivamente em humanos, e, mas recentemente, em cães e gatos. Estes anticorpos podem reduzir a especificidade de testes alérgicos sorológicos in vitro . Objetivos – Investigar a prevalência de imunoglobulina (Ig)E tanto em cavalos alérgicos quanto em cavalos não alérgicos e avaliar o seu potencial impacto no teste alérgico sorológico. Animais – Vinte e um cavalos alérgicos e 21 não alérgicos. Métodos e materiais – O soro foi testado para IgE anti‐CCD utilizando um ensaio imunoenzimático CHO comercial (ELISA). Um ELISA alérgeno‐específico para receptor Fc‐ε foi realizado para avaliar polissensibilização, com e sem a adição de uma solução de bloqueio anti‐CCD. Resultados – Anticorpos anti‐CCD foram encontrados em 30 de 42 cavalos. Não houve diferença estatística significativa ( P = 0, 18) entre os grupos alérgico e saudável quanto à prevalência de anti‐CCD. Cavalos com IgE anti‐CCD exibiram mais polissensibilização no teste alérgico sorológico que cavalos sem IgE anti‐CCD em todos os grupos alergênicos, exceto ácaros. Polissensibilização foi estatisticamente significativa em um intervalo de confiança de 95% para gramíneas ( P < 0, 03), herbáceas ( P = 0, 02) e insetos que picam ( P = 0, 0005). Isto foi verdadeiro para os dois grupos estudados. Inibição com uma solução bloqueadora de anti‐CCD resultou em uma redução média de 43% na polissensibilização. Conclusão e importância clínica – A prevalência de IgE anti‐CCD em cavalos nesse estudo coincide com a prevalência detectada em pessoas sensibilizadas a pólen. Equinos com IgE anti‐CCD apresentaram mais reações positivas nos testes alérgicos sorológicos. Minimizando uma potencial polissensibilização a partir da utilização de um bloqueador de anti‐CCD pode facilitar a identificação de IgE alérgeno‐específica.